Genetic and clinical characterization of B7‐H3 (CD276) expression and epigenetic regulation in diffuse brain glioma. Issue 9 (29th August 2018) - Wang, Zhiliang; Wang, Zheng; Zhang, Chuanbao; Liu, Xing; Li, Guanzhang; Liu, Shuai; Sun, Lihua; Liang, Jingshan; Hu, Huimin; Liu, Yanwei; Zhang, Wei; Jiang, Tao
Abstract : Gliomas are the most common malignant tumors of the brain. Immune checkpoints have been increasingly emphasized as targets for treating malignant tumors. B7‐H3 has been identified as an immune checkpoint that shows potential value for targeting therapies. We set out to characterize the expression pattern and biological function of B7‐H3 in brain gliomas using high‐throughput data obtained from the Chinese Glioma Genome Atlas (CGGA) and the Cancer Genome Atlas (TCGA) projects. B7‐H3 was upregulated more in higher‐grade gliomas than that in lower‐grade gliomas in both CGGA and TCGA datasets. Isocitrate dehydrogenase (IDH) mutation seemed to exert significant influence on B7‐H3 expression in gliomas but led to quite different results between grade II gliomas and higher‐grade gliomas. In addition to IDH, methylation of B7‐H3 promoter and microRNA‐29 family also showed a potential regulatory effect on B7‐H3 expression. Gene ontology analysis revealed that B7‐H3 was associated with mitotic cell cycle, cell proliferation and immune response. Further investigation suggested that B7‐H3 was mostly involved in the Toll‐like receptor signaling pathway. Survival analysis indicated that B7‐H3 was an independent unfavorable prognosticator for glioma patients in both CGGA and TCGA datasets. B7‐H3 expression is regulated by multiple mechanisms and is potentially involved in the T‐cell receptor signaling pathway. Higher B7‐H3 expression indicates a worse prognosis for glioma patients, which warrants further research into the development of inhibitors for targeting this immune checkpoint, but we still need to be cautious about immune checkpoint inhibition for central nervous system tumors. Abstract : B7‐H3 expression is regulated by multiple mechanisms and is mainly involved in the T‐cell receptor signaling pathway. Higher B7‐H3 expression indicates worse prognosis for glioma patients, which warrants further research into the development of inhibitors for targeting this immune checkpoint, but we still need to be cautious about immune checkpoint inhibition for central nervous system tumors.